Padel, pickleball and wellbeing: a systematic review - Lauxtermann, Lena; Stubbs, Brendon (Frontiers in Psychology, 2025)
IntroductionPhysical activity benefits mental health, yet the effects of emerging sports like padel and pickleball are understudied despite their accessibility and growth—300,000 amateur padel players worldwide and a 223.5% rise in U. S. pickleball players (2020–2023). This systematic review examines their association with mental health, wellbeing, and mental fatigue.MethodsAn electronic search of Medline, PsycINFO, and Embase (inception to October 8, 2024; PROSPERO CRD42024594743) identified quantitative and observational studies on padel or pickleball participation and mental health or wellbeing outcomes.ResultsFourteen of 71 studies (n = 1,403) were included. Pickleball enhances wellbeing, life satisfaction (p < 0.05), happiness (r = 0.263, p < 0.001), depression (r = −0.23, p < 0.01), and social integration, especially in older adults. In padel, higher-level and match-winning players show increased self-confidence and reduced somatic anxiety; pre-competition anxiety rises, varies by gender and score, and is lower than in tennis. Mental fatigue increases with successive padel games, impairing accuracy (p = 0.05) and linking to elevated motivation.ConclusionMental health research on padel and pickleball has expanded, revealing distinct areas of focus. Padel studies primarily target performance aspects like self-confidence, anxiety, and mental fatigue, while pickleball research highlights wellbeing gains in life satisfaction, happiness, and social integration. However, gaps remain, particularly regarding the exploration of wellbeing in padel and performance-related mental health (e.g., anxiety, fatigue) in pickleball across diverse age groups to address these gaps. Future studies should address these gaps and consider diverse age groups to provide a more comprehensive understanding.Systematic review registrationPROSPERO: The Unique Identifier is CRD42024594743, and the publicly accessible URL is https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024594743.